Sales Forecasting by Using Exponential Smoothing Method and Trend Method to Optimize Product Sales in PT. Zamrud Bumi Indonesia During the Covid-19 Pandemic - Virgin Wineka Nirmala; Dikdik Harjadi; Robi Awaluddin (International Journal of Engineering, Science and Information Technology, 2021)
Forecasting is important for a company in achieving goals effectively and efficiently. Forecasting aims to determine the next steps to be taken based on historical data. PT. Zamrud Bumi Indonesia is one of the manufacturing companies in the management of agricultural liquid fertilizers with the trademark “Power Bumi”. The purpose of this study is to analyze the sales pattern of Power Bumi products during the covid-19 pandemic and compare the forecasting method that is able to produce the smallest error value in forecasting sales of Power Bumi products PT. Zamrud Bumi Indonesia. This study uses 2 methods, namely exponential smoothing and least square trend model. To calculate the error rate using MAD, MSE and MAPE. The results show that the exponential smoothing alpha 0.9 method has the smallest error value compared to other forecasting methods. In forecasting product sales, the MAD value is 130.329, MSE is 28251.23 and MAPE is 22.00% with a forecast of 627.628 boxes. Although the exponential smoothing a 0.9 method produces a forecast value that is relatively low than other methods. However, the comparison of products sold and forecasting results has a relatively small average difference (MSE). It can be interpreted that the exponential smoothing a 0.9 method is able to suppress the forecasting error value for the 2nd period. After getting the forecasting results, it can be concluded that the number of products sold for the 2nd covid-19 pandemic period will not differ much from the number of sales in the 1st covid-19 pandemic period. If the company applies this scientific forecasting method, then sales will be optimal so that excess or shortage of stock can be avoided and the predetermined sales target can be achieved. In addition, the costs incurred during the production process to sales will be more efficient.